2020
DOI: 10.1089/acm.2019.0113
|View full text |Cite
|
Sign up to set email alerts
|

Shi-Style Cervical Mobilizations Versus Massage for Cervical Vertigo: A Multicenter, Randomized, Controlled Clinical Trial

Abstract: Objectives: Large sample and high-quality evidence to evaluate the preliminary safety of the mobilizations and massage for cervical vertigo are not yet available. Thus, the present study aimed to investigate the comparative effectiveness and preliminary safety of Shi-style cervical mobilizations (SCM) compared with traditional massage (TM) in cervical vertigo patients. Design: A prospective, multicenter, open-label, randomized, controlled clinical trial with a 1:1 allocation ratio. Settings: Five academic medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Evidence-Based Complementary and Alternative Medicine erefore, this disease is the syndrome of deficiency in nature and excess in superficiality. Based on this, when formulating clinical treatment, we can start from the ideas of suppressing hyperactive liver for calmingendogenous wind, benefiting Qi and activating blood circulation, and disperse blood stasis and dredge collateral [15].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence-Based Complementary and Alternative Medicine erefore, this disease is the syndrome of deficiency in nature and excess in superficiality. Based on this, when formulating clinical treatment, we can start from the ideas of suppressing hyperactive liver for calmingendogenous wind, benefiting Qi and activating blood circulation, and disperse blood stasis and dredge collateral [15].…”
Section: Discussionmentioning
confidence: 99%
“…Detailed design and clinical results of Trial A and Trial B have been reported ( Cui et al, 2013 ; Yao et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Data handling rules and full analysis methods were previously described in Cui et al (2013) and Yao et al (2020) . Standard statistical techniques will be used to describe the characteristics of patients in both groups.…”
Section: Methodsmentioning
confidence: 99%
“…There has been extensive reporting on physical therapy for the neck as treatment for CV [ 78 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 ], though, “Regarding the treatment of proprioceptive cervical vertigo, in which pain and imbalance or vertigo are the limiting symptoms, the quality of published studies in the current literature is poor” [ 6 ].…”
Section: Treatmentmentioning
confidence: 99%